Behavioral Economics: A Primer and Applications to the UN Sustainable Development Goal of Good Health and Well-Being - Robert Siegel (Reports, 2021)
Behavioral economics (BE) is a relatively new field within economics that incorporates insights from psychology that can be harnessed to improve economic decision making with the potential to enhance good health and well-being of individuals and societies, the third of the United Nations Sustainable Development Goals. While some of the psychological principles of economic decision making were described as far back as the 1700s by Adam Smith, BE emerged as a discipline in the 1970s with the groundbreaking work of psychologists Daniel Kahneman and Amos Tversky. We describe the basic concepts of BE, heuristics (decision-making shortcuts) and their associated biases, and the BE strategies framing, incentives, and economic nudging to overcome these biases. We survey the literature to identify how BE techniques have been employed to improve individual choice (focusing on childhood obesity), health policy, and patient and healthcare provider decision making. Additionally, we discuss how these BE-based efforts to improve health-related decision making can lead to sustaining good health and well-being and identify additional health-related areas that may benefit from including principles of BE in decision making.